Marketing analysis of enterprise product policy: objectives, tasks, prospects (Economics and region, 2024)
The product is presented as a central element in the complex of enterprise marketing, so the analysis of product policy is the key in the system of marketing analysis. Understanding of the product differs for an economist and a marketer, as the latter focuses on the consumer-oriented characteristics or benefits provided by the product. Product policymaking requires comprehensive marketing analysis as it involves different aspects from different perspectives and addresses a few challenges. The article identifies the goals and tasks of the product policy marketing analysis. It has been proved that the objective of the marketing analysis is a comprehensive analysis of the individual product by its structural elements. It is emphasized that it is important to assess the profit margin of goods from the point of view of the enterprise, and marketers use different indicators for that purpose. Marketing analysis of the consumer value of products, their brands and life cycle is also a significant aspect of the product policy. The author emphasizes that marketers use different methods and models to estimate the consumer value of the product, such as the Rosenberg model, perception map, semantic differential, and others. Brand or trademark analysis is carried out through positioning and brand equity analysis. In this context, the marketing analysis of the enterprise’s product policy is supplemented by the study of the customer loyalty and factors that influence its changes. The study of the product’s life cycle and its changes is also the important part of the marketing analysis. It is pointed out that the analysis of the product policy in marketing reflects a complex process that requires careful study of many aspects and solution of various tasks of the enterprise. Product selection, pricing, positioning strategy and communication channels play important roles in product policy research. The analysis of these factors helps the enterprise to gain a better understanding of market conditions, consumer needs and competitive situation, which becomes the basis for the development of effective strategies for development and increasing competitiveness. Thus, the product policy marketing analysis is an essential stage of management of the enterprise market activities, contributing to the success in the market by the better understanding of its conditions and requirements.
Keywords: marketing analysis; product; marketing commodity policy; product range; brand; consumer value; product brand; customer loyalty